Local demand-pull policy and energy innovation: Evidence from the solar photovoltaic market in China - Gao, Xue; Rai, Varun (Energy policy, 2019)
Market demand is an important driver for inducing innovation, with many empirical studies supporting the demand-induced innovation hypothesis. Critiques of such studies, however, emphasize that new empirical evidence that can address existing empirical challenges is needed. Furthermore, existing literature disagrees about whether the locus of demand-pull policy matters. In this paper, we use empirical evidence from the distributed solar photovoltaic (PV) market in China to address the following questions: (1) Is there evidence of demand-induced innovation? (2) Does the effect of local demand-pull policy differ from the effect of non-local demand-pull policy on demand-induced innovation? To address these questions, we develop and analyze an original database of PV balance-of-system (BOS) patents in the distributed PV market filed between 2005 and 2014 in China. Our results support the demand-induced innovation hypothesis and suggest that only local demand significantly induces PV BOS innovations in the distributed PV market in China. The different effects of local demand and non-local demand emphasize the importance of local markets and local policies, lending some support to bottom-up approaches to clean energy governance. •Developed an original dataset of non-module solar photovoltaic patents in China.•We exploit subnational variation in demand-pull policies and patenting activity.•Effects of local and non-local demand on innovations differentiated.•Technology characteristics mediate the role of local demand in inducing innovation.•Findings lend support to bottom-up approaches to clean energy governance.